PENGARUH PENAMBAHAN TEPUNG KARAGENAN TERHADAP SIFAT KIMIA OTAK-OTAK IKAN GABUS (Ophiocephalus striatus) - Siti Nur Aisyah Jamil (Samakia : Jurnal Ilmu Perikanan, 2016)
Sneakhead fish is one kind of freshwater fish which are content of albumin. The extractor vacuum was used to extract the fish into albumin. Moreover, the extraction produced residue product, the meat, which was still nutritious even though it could not be more extracted. This residue product was then processed into fish otak-otak. This study was aimed to know the effect of the addition of carrageenan powder on the the chemical nature and organoleptic test of sneakhead fish otak-otak. The treatments used in this research were the variation treatment of addition of carrageenan powder on the of its albumin, protein, crute fiber, carbohydrate, fat, moisture, ash content and organoleptic test (smell, taste, color, texture). The results of research were analyzed three times by using completely randomized design (ral). The results showed that different addition of carrageenan powder give a significant effect on the chemical nature of sneakhead fish otak-otak. The best treatment was obtained at addition of carrageenan powder concentration 10% (e) with an average value of albumin content 1,7%, 7,2% protein content; crute fiber of 2,16%, carbohydrate of 45,24%, fat content of 0,78%, 45,45% water content; 1,28% ash content.